Hydraulic engineering II proceedings of the 2nd Sree Conference on Hydraulic Engineering (CHE 2013), Hong Kong, 2-3 November 2013 - Xie, Liquan 1972- (CRC Press/Balkema, 2013)
Hydraulic research is developing beyond traditional civil engineering, since the number of natural hazards increased in recent years, and so did the extent and scope of structural safety assessment and environmental research. Hydraulic Engineering II contains 44 technical papers from the 2nd SREE Conference on Hydraulic Engineering (CHE 2013, Hong Kong, 2-3 November 2013, including the Third SREE Workshop on Environment and Safety Engineering, WESE 2013), discusses recent advances and issues, and identifies challenges associated with engineering applications in hydraulic engineering